Disulfiram Protects Against Radiation-Induced Intestinal Injury in Mice - Yuan, Qingwen; Peng, Renjun; Yu, Huijie; Wang, Sinian; Chen, Zhongmin; Dong, Suhe; Li, Wei; Cheng, Bo; Jiang, Qisheng; Cong, Yuwen; Li, Fengsheng; Li, Changzheng (Frontiers in Pharmacology, 2022)
Radiation-induced intestinal injury (RIII) occurs after high doses of radiation exposure. RIII restricts the therapeutic efficacy of radiotherapy in cancer and increases morbidity and mortality in nuclear disasters. Currently, there is no approved agent for the prevention or treatment of RIII. Here, we reported that the disulfiram, an FDA-approved alcohol deterrent, prolonged the survival in mice after lethal irradiation. Pretreatment with disulfiram inhibited proliferation within 24 hours after irradiation, but improved crypt regeneration at 3.5 days post-irradiation. Mechanistically, disulfiram promoted Lgr5+ intestinal stem cells (ISCs) survival and maintained their ability to regenerate intestinal epithelium after radiation. Moreover, disulfiram suppresses DNA damage accumulation, thus inhibits aberrant mitosis after radiation. Unexpectedly, disulfiram treatment did not inhibit crypt cell apoptosis 4 hours after radiation and the regeneration of crypts from PUMA-deficient mice after irradiation was also promoted by disulfiram. In conclusion, our findings demonstrate that disulfiram regulates the DNA damage response and survival of ISCs through affecting the cell cycle. Given its radioprotective efficacy and decades of application in humans, disulfiram is a promising candidate to prevent RIII in cancer therapy and nuclear accident.